Antioxidant activity and preference level of aloe vera (Aloe vera var. chinensis) beverages made with gel size and boiling time variation: Aktivitas Antioksidan dan Tingkat Kesukaan Minuman Gel Lidah Buaya (Aloe vera var. chinensis) yang dibuat dengan Variasi Ukuran Gel dan Lama Perebusan - Imani, Meida Indika; Chatarina Wariyah; Yulianto, Wisnu Adi (Universitas Slamet Riyadi Surakarta, 2025)
Aloe vera gel contains antioxidative phenolic compounds. Fresh aloe vera gel is less accepted by the community due to its bitter taste from its latex. An acceptable alternative to aloe vera products is an aloe vera gel beverage because people of all ages currently favor light drinks. This study aims to produce aloe vera gel beverages with high antioxidant content by varying the gel size and boiling duration for easy consumption and preference by panelists. This research employed a completely randomized design (CRD) with two treatment factors, namely variations in gel size (0.5x1 cm, 1x2 cm, 2x3 cm) and boiling duration (10 minutes, 15 minutes, 20 minutes). The obtained data were subsequently analyzed Analysis of Variance (ANOVA). If differences were found, Duncan's Multiple Range Test (DMRT) was conducted at a significance level of 5%. The research results indicate that variations in gel size and boiling duration affect antioxidant activity, moisture content, total sugar content, gel texture, and preference level. The acceptable aloe vera gel beverage, preferred by the panelists which made with a gel size of 0.5x1 cm and a boiling duration of 10 minutes, with exhibited the highest antioxidant activity 6.72% RSA, moisture content 94.15%, total sugar content 13.35%, hardness (6.25 g/cm2, and deformation 2.81 mm.